Unifying Artifacts and Activities in a Visual Tool for Distributed Software Development Teams - Froehlich, Jon; Dourish, Paul (International Conference on Software Engineering: Proceedings of the 26th International Conference on Software Engineering; 23-28 May 2004, 2004)
In large projects, software developers struggle with two sources of complexity the complexity of the code itself, and the complexity of of the process of producing it. Both of these concerns have been subjected to considerable research investigation, and tools and techniques have been developed to help manage them. However, these solutions have generally been developed independently, making it difficult to deal with problems that inherently span both dimensions.We describe Augur, a visualization tool that supports distributed software development processes. Augur creates visual representations of both software artifacts and software development activities, and, crucially, allows developers to explore the relationship between them. Augur is designed not for managers, but for the developers participating in the software development process.We discuss some of the early results of informal evaluation with open source software developers. Our experiences to date suggest that combining views of artifacts and activities is both meaningful and valuable to software developers.